IMPROVING VIDEO QUALITY WITH ARTIFICIAL INTELLIGENCE (Conferencea, 2021)
Image Enhancement is the process of improving the image quality without loss of information until the desired visual result (resolution, color and style) is obtained or the photo is prepared for further analysis in various computer vision programs: object recognition, classification, image interpretation. Image quality improvement usually includes a number of transformations: noise reduction, improvement of blurred photos, increase in resolution, contrast, lightening of dark photos, elimination of optical distortions, etc